Long-Term Harmful Algal Blooms and Nutrients Patterns Affected by Climate Change and Anthropogenic Pressures in the Zhanjiang Bay, China - Zhang, Peng; Peng, Conghui; Zhang, Jibiao; Zhang, Junxiao; Chen, Jiyu; Zhao, Hui (Frontiers in Marine Science, 2022)
Climate change and anthropogenic pressures have significantly affected coastal environments. This study obtained historical data on harmful algal blooms (HABs) and nutrient patterns over a 30-year period to explore responses to long-term climate change and anthropogenic pressure indicators. Although the surrounding area has achieved great economic success over the past 30 years, the Zhanjiang Bay (ZJB) has been seriously affected by various pollutants and is threatened by increasing eutrophication and HABs due to climate change and anthropogenic pressures. In the ZJB, HABs rarely occurred before the 1980s but have occurred periodically and frequently since the 2000s. The largest HAB covered an area of 310 km2 in 2005. Most of the HABs occurred during spring. Additionally, the dominant phytoplankton species were Skeletonema costatum and Phaeocystis globosa, accounting for 37.50% and 43.75% of the HABs observed, respectively. Anthropogenic pressures have caused the nutrient regime to significantly increased in the ZJB over the past three decades (P<0.05). Specifically, the concentration of dissolved inorganic nitrogen (DIN) increased 3-fold from the beginning of the 1990 to 2019 period, while the dissolved inorganic phosphorus (DIP) concentration increased 21-fold. Unsynchronized variation in nutrient patterns has led to changes in the composition of nutrients, and the ZJB ecosystem has shifted from a P-limited oligotrophic state before the 2000s to an N-limited eutrophic state. Anthropogenic pressure indicators showed a significant linear correlation with nutrients (P<0.05), but climate change indicators did not play a direct role in the eutrophication problem in the ZJB during this period (P>0.05). Therefore, integrated land-ocean environment management should be introduced to reduce land-based pollution sources, mitigate eutrophication, and curb the blooms of harmful algae in the ZJB.